How Aborigines Invented the Idea of Contemporary Art: Writings on Aboriginal Contemporary Art - McLean, Ian (Institute of Modern Art, 2011)
Chronicles the global critical reception of Aboriginal art since the early 1980s and argues for a re-evaluation of Aboriginal art's critical intervention into contemporary art.
OCLC: 762144288
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude de la réception; 3-Océanie (corpus analysé); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé